A Transatlantic Energy and Climate Pact Is Now More Necessary Than Ever - Klaas Lenaerts; Simone Tagliapietra (Intereconomics, 2022)
The Russian invasion of Ukraine has pushed Europe to re-design its energy map at speed. Amid this unprecedented energy overhaul, the EU and the United States have flagged their commitment to reinforce their bilateral energy partnership, starting with short-term measures to boost US liquefied natural gas supplies to Europe to promptly replace part of Russian gas imports. This article develops five issues around which a stronger transatlantic energy and climate pact might be built.
Keywords: Q40; Q42; Q48; 330